Unveiling Smartphone Brand Switching: Insights from Consumer Behavior Analysis - Shrestha, Sajeeb Kumar (MultiTech Publisher, 2024)
This study investigates the factors impacting brand switching within the smartphone category using both descriptive and causal research designs. Data from 200 participants were collected through structured questionnaires in a survey format, focusing on customers who recently changed their smartphones. Analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Hayes Process Macros to assess moderation effects. Results indicated that customer innovation and pricing significantly influence brand switching, while product features, referrals, and marketing strategies were found to have negligible effects, indicating a lack of perceived value for customers. Additionally, gender was found to moderate the relationship between product features, marketing strategies, and brand switching. The findings of this research hold implications for marketers, emphasizing the importance of understanding demographic profiles to effectively prevent brand switching and develop competitive strategies in the smartphone market.